Size and bathymetry of Greiner Lake and other large lakes in its watershed, Nunavut ... : Taille et bathymétrie du lac Greiner et des grands lacs dans son bassin versant, Nunavut ... - Rautio, Milla; Lapeyre, Juliette; Ayala Borda, Paola; Grosbois, Guillaume; Moore, Jean-Sebastien; Harris, Les N.; Malley, Brendan K.; Blackburn-Desbiens, Pénélope (Nordicana D, 2022)
Most of the world’s lakes are in the Arctic, yet very little is known about these aquatic environments. We present here the size and depth data for five large lakes in the Greiner lake watershed near Cambridge Bay, southern Victoria Island, Nunavut. Using satellite imagery, a watershed digital surface model (WDSM) was generated to estimate surface area of Greiner lake, First lake, Second lake, Inuhuktok and Nakyulik. Bathymetry for each lake was generated using depth measures that were taken as point measures and a Biosonics or Humminbird echo sounder. ... : La majorité des lacs du monde se trouvent en Arctique, mais on sait pourtant très peu de choses sur ces milieux aquatiques. Nous présentons ici des données sur la taille et la profondeur de cinq grands lacs du bassin versant du lac Greiner, près de Cambridge Bay, dans le sud de l'île Victoria, au Nunavut. À l'aide d'images satellitaires, un modèle numérique de surface du bassin versant (WDSM) a été généré pour estimer la superficie des lacs Greiner, First, du Second, Inuhuktok et Nakyulik. La bathymétrie de chaque lac a été générée à l'aide de mesures de profondeur prises sous forme de mesures ponctuelles et d'un échosondeur Biosonics ou Humminbird. ...